1989
DOI: 10.1088/0268-1242/4/4/031
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate valency state of samarium chalcogenides under high pressure

Abstract: Samarium chalcogenides undergo isostructural phase transitions under pressure and samarium ions turn into an intermediate valency state (IVS).The thermo EMF S and electroresistance p of SmS, SmSe and SmTe under pressure to 12 GPa and in the temperature range 30-400 "C have been measured to investigate properties of the IVS and its stability limits. Hydrostatic pressure to 8 GPa and quasi-hydrostatic pressure to 12 GPa on monocrystals have been realised in 'toroid' cells. It is found that the IVS is stabilised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…B2 transition is accompanied by a valence change in the pressure range of 6-8 GPa. Sidorov et al [3] have reported similar valence transition at 5.2 GPa. To our knowledge, no theoretical studies have been performed on the structural properties at high pressures.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…B2 transition is accompanied by a valence change in the pressure range of 6-8 GPa. Sidorov et al [3] have reported similar valence transition at 5.2 GPa. To our knowledge, no theoretical studies have been performed on the structural properties at high pressures.…”
Section: Introductionmentioning
confidence: 69%
“…In the recent past, the rare-earth chalcogenides (RECs) have attracted experimental [1][2][3][4][5] and theoretical attention [6][7][8] due to their interesting structural, optical, mechanical and electronic properties. Out of these RECs, Samarium mono-chalcogenides SmX (X ¼ S, Se, Te) have been investigated in greater detail in view of their technological applications [1,2] in spintronic and spin filtering devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoemission experiments show distinctly different spectra for the two phases, which usually are interpreted on the basis of divalent f 6 ions in the ground state and mixed valent f 5 -f 6 ions in the high pressure metallic phase [17,18]. Similar valence instabilities are observed in SmSe and SmTe [13,17,19,2], which also crystallize in the NaCl structure. For these compounds the volume changes continuously, but anomalously, with pressure (at room temperature) [20,2].…”
Section: Introductionmentioning
confidence: 80%
“…7 The C 12 elastic constant decreases with pressure 17 and becomes negative in the high pressure phase, indicative of an intermediate valence system. 1 The pressure-induced semiconductor to metal transformation has also been traced by optical reflectivity studies, 18 Mössbauer measurements, 19 resistivity measurements, 20 and inelastic x-ray scattering. 8 Valence transitions can also be brought about by alloying with other trivalent ions, such as Y, La, Ce, or Gd, into the SmS lattice.…”
Section: Introductionmentioning
confidence: 99%